2020
DOI: 10.1186/s12938-020-00829-5
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour real-time continuous monitoring of acute focal cerebral ischemia in rabbits based on magnetic inductive phase shift

Abstract: Background As a serious clinical disease, ischemic stroke is usually detected through magnetic resonance imaging and computed tomography. In this study, a noninvasive, non-contact, real-time continuous monitoring system was constructed on the basis of magnetic induction phase shift (MIPS) technology. The “thrombin induction method”, which conformed to the clinical pathological development process of ischemic stroke, was used to construct an acute focal cerebral ischemia model of rabbits. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, the early AIS detection method based on the development of near-field coupling technology meets the current clinical needs and has the theoretical feasibility. Our previous 24 h monitoring experimental study on focal ischemia of rabbits based on NFC shows that the time of infarct caused by local ischemia is about 5–6 h [ 32 ]. Combined with the time window of thrombolytic therapy, we carried out an experimental study of AIS monitoring within a 6 h time window based on multi-parameter near-field coupled sensing in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the early AIS detection method based on the development of near-field coupling technology meets the current clinical needs and has the theoretical feasibility. Our previous 24 h monitoring experimental study on focal ischemia of rabbits based on NFC shows that the time of infarct caused by local ischemia is about 5–6 h [ 32 ]. Combined with the time window of thrombolytic therapy, we carried out an experimental study of AIS monitoring within a 6 h time window based on multi-parameter near-field coupled sensing in this work.…”
Section: Discussionmentioning
confidence: 99%
“…One of the electromagnetic induction methods is magnetic induction phase shift (MIPS) measurement, which could realize non-invasive, non-contact, depth, and bedside monitoring of whole brain electrical properties. The MIPS measurement has been applied to detect cerebral ischemia, cerebral edema, cerebral hemorrhage, and cerebral trauma on the principle that the obtained MIPS is proportional to the conductivity of the brain tissue in the field [ 32 35 ]. Previous studies have confirmed that the MIPS signal changes proportionally with CBV changes [ 36 , 37 ], and the contactless electromagnetic induction measurement is sensitive enough to detect CVAR [ 38 ], but whether a novel index based on the MIPS method can be established to assess CVAR with spontaneous oscillations blood pressure requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic induction phase shift (MIPS) technology is a method that could realize noninvasive, noncontact, whole-brain, deep part, and real-time continuous monitoring 23,24 . It is based on MIPS being proportional to the conductivity of measured brain tissues 25 .…”
Section: Introductionmentioning
confidence: 99%